Increased Prevalence of Alloimmunization in Sickle Cell Disease? Should We Restore Blood Donation in French Guiana? - Conrath, Salomé; Vantilcke, Vincent; Parisot, Mickael; Maire, Françoise; Selles, Pierre; Elenga, Narcisse (Frontiers in Medicine, 2021)
Patients with sickle cell disease often undergo frequent blood transfusions. This increases their exposure to red blood cell alloantigens of donor units, thus making it more likely that they produce alloantibodies. This cross-sectional study aimed to describe the prevalence of allo-immunization in patients with sickle cell disease who were monitored at Cayenne Hospital in 2016. Of the 451 patients recruited during the study period, 238 (52.8%) were female. There were 262 (58.1%) homozygous sickle cell and 151 (33.5%) compound heterozygous sickle cell patients. The median age of the participants was 23.09 years (range, 0.5-68). We noted different red blood cell extended phenotypes: -in the Duffy system, the Fya- Fyb - profile was found in 299 patients (66%); - for the Kidd system, the most represented profile was Jka+ Jkb-, with 213 patients (47%). The Jka antigen was present in 355 patients; - in the MNS system, the S-s+ profile was found in 297 patients (66%); - the Lea antigen of the Lewis system was absent in 319 patients. The most frequent Rh phenotype in our patients was D+ C- E- c+ e+ K-, representing 51% of the patients. A total of 6,834 transfused packed red blood cell units were recorded. Sixty-eight patients (23%; 95% confidence interval, 20-25%) had detectable RBC alloantibodies. In multivariate logistic regression, only the mean number of single transfusions was statistically higher for the alloimmunized patients (p < 0.04). Thirteen (19%) of the patients with alloimmunization developed a delayed hemolytic transfusion reaction, thus representing 4.4% of the total number of transfused patients. There was disparity between the blood received from France versus the recipients in French Guiana. In conclusion, careful transfusion strategies for patients with RBC alloantibodies should allow further reduction of the rate of alloimmunization.